Economic Development and Islamic Finance - Iqbal, Zamir (World Bank, 2015)
Over the last three decades, the concepts of Islamic finance and Islamic economics have captured the attention of researchers. The growing market for transactions compatible with Islamic law (Shari-áh) is further evidence of growing interest in this mode of finance. By some estimates, the total volume of Islamic financial assets has grown by 15 to 20 percent a year since 1990 and now exceeds $1.3 trillion. The growth of the Islamic financial sector in 2006?10 period surpassed the growth of conventional financial sector in all segments of the market, ranging from commercial banking, investment banking, and fund management to insurance in several Muslim-majority countries. The growth of this market has been driven by the high demand for Shari-áh-compliant products, as well as the increasing liquidity in Gulf region due to high oil revenues. Following on from the significant developments that have occurred in what is viewed as the core area for this market?the predominantly Muslim countries?we are now witnessing the globalization of Islamic finance. In recent years, significant interest in Islamic finance has emerged in the world?s leading conventional financial centers, including London, New York, and Hong Kong, and Western investors are increasingly considering investment in Islamic financial products. Although Islamic finance is one of the fastest growing segments of emerging global financial markets, it is often stated that the market is far below its true potential. At the same time, the concepts of Islamic finance are not fully explained and exploited?especially in the areas of economic development, inclusion, access to finance, and public policy. This volume attempts to highlight some of the key features of Islamic finance relevant to economic development. The objective of the volume is to improve understanding of the perspective of Islamic finance on economic development, social and economic justice, human welfare, and economic growth.